Practices for New Research University's Collaborative Collection Development of Print and Electronic Books: A Case Study of SUSTech Library - Feiyan HUANG (Nongye tushu qingbao xuebao)
[Purpose/Significance] With the rapid development of international academic digital publishing, ebook sales have surpassed those of print books since 2020. Many academic libraries in the USA are adopting e-preferred book collection development policies. In recent years, China's academic ebook market has been growing rapidly, as the well-known academic publishers such as Science Press and Tsinghua University Press have successively launched their own ebook platforms, and high-quality ebook integrator platforms such as Keledge and Cxstar have emerged, leading to a qualitative leap in both the quality and quantity of Chinese academic ebooks. The rapid development of the Chinese and English ebook markets has made collaborative collection development of print and ebooks feasible, which is considered to be a good solution to the tight collection budget and insufficient library space for Chinese academic libraries. The paper aims to propose a strategic direction and implementation path for collaborative collection development of print and ebooks, and provide a reference for the high-quality development of academic library collection development under the background of "Double First Class" construction. [Method/Process] The paper summarizes the main characteristics of SUSTech Library's three phases of book collection development, and introduces SUSTech Library's collaborative collection development practices of print and ebooks from four aspects: collaborative acquisition, collaborative management, collaborative services, and collaborative evaluation. A collaborative acquisition strategy should be based on four factors: collection assurance, patron needs, library space, and cost effectiveness. Collaborative management should redesign the business process from the aspects of funding plan, book selection, acquisition implementation, metadata management, and statistics. Collaborative services should be based on the needs, recommendations, and usage of user groups and individual users. Collaborative evaluation refers to a structured analysis on the print and ebook collections across five dimensions, including language, subject, publisher, book type, and year of publication. [Results/Conclusions] The paper puts forward suggestions from three aspects, such as top-level design, deep integration of business processes, and integrated management platforms. The academic libraries' management team should develop collaborative collection development policies and strategies from the top down. Deep integration of business processes should support optimization of organizational structure and job position adjustment, which replaces the traditional approach of defining job positions and responsibilities based on a single material type or business process. Integrated management platforms should support the integration of multiple metadata sources and business processes, and have strong knowledge discovery and service capabilities.